2020
DOI: 10.9734/ajeba/2020/v19i230298
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Macroeconomic Variables on Bank Credit in Saudi Arabia: An ARDL Bounds Testing Approach to Cointegration

Abstract: The main objective of the paper is to examine the relationship between bank credit and the major macroeconomic variables of Saudi Arabia during the period from 1993 to 2019. An autoregressive distributed lag (ARDL) method was employed to estimate the short-run and long-run effects of the major macroeconomic variables on bank credit. The study revealed that the real exchange rate and money supply have positive long-run effects on bank credit compared to the negative effects of inflation on bank credit. Gross do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…Both tables show that in all cases, the unit root hypothesis cannot be rejected. Therefore, It can be concluded that most variables are I (1), except for trade balance, which was stationary at level, a result confirmed by numerous other studies such as Ibrahim and Bashir [36]; Bashir and Ibrahim, [50]; Ibrahim and Bashir, [53]; Wu [54].…”
Section: Unit Root Testssupporting
confidence: 75%
See 1 more Smart Citation
“…Both tables show that in all cases, the unit root hypothesis cannot be rejected. Therefore, It can be concluded that most variables are I (1), except for trade balance, which was stationary at level, a result confirmed by numerous other studies such as Ibrahim and Bashir [36]; Bashir and Ibrahim, [50]; Ibrahim and Bashir, [53]; Wu [54].…”
Section: Unit Root Testssupporting
confidence: 75%
“…If the unit root analyses suggest that all the variables are I(1) and the residuals in the model are stationary, we can conclude that the series are cointegrated in order I(1). The advantage of cointegration and error correction techniques is that they provide more efficient short-run and long-run coefficient estimates and avoid the problems of spurious regression [50]. The ARDL bounds testing procedure is sensitive to the selection of the lag structure.…”
Section: Cointegration Processmentioning
confidence: 99%